Peranan dan Strategi Bank Sentral dalam Menjaga Stabilitas Sistem Keuangan - Dea Dellia; Dwi Ananda; Lilis Apriyaningsih; Windi Aulia; Dwita Sakuntala (Journal Economic Excellence Ibnu Sina, 2025)
The article discusses the role and strategies of the Central Bank and the Government in maintaining financial system stability, which is crucial for the effective functioning of market economies. A stable financial system is essential for rational decision-making regarding resource allocation and enhancing the investment climate. Historical experiences, particularly Indonesia's financial crisis in 1998 and the global financial crisis in 2008, highlight the high costs associated with financial instability and the importance of implementing both microprudential and macroprudential policies to prevent such crises. The Central Bank of Indonesia (Bank Indonesia) plays a vital role in this regard by regulating monetary policy, overseeing financial institutions, and ensuring a robust payment system. It employs various indicators to measure financial stability, including capital adequacy ratios and economic growth metrics. The article emphasizes that stability in the financial system not only fosters investor confidence but also supports efficient financial intermediation, ultimately contributing to sustainable economic growth.